Nitriding in low carbon steels using non-toxic salt baths - Bonow, Vinicius Timm; Maciel, Débora Stefani; Zimmer, André; Zimmer, Cinthia Gabriely (Revista Liberato, 2019)
The objective of this article is to develop a method of nitriding in non-toxic salt baths, using potassium nitrate (KNO3) and sodium nitrite (NaNO2), as well as to evaluate the hardness and the visual aspect of the surface layer of a steel with 0.2% carbon, seeking for an alternative to reduce the environmental impact caused by the conventional process of nitriding in salt bath containing cyanide and cyanate. It was also studied some means that can reduce the non-adherent oxides generated during the nitriding process. The results indicate that the salts KNO3 and NaNO2 act in the formation of a nitrated layer, evidenced by a microstructural change and the increase of the layer hardness, in relation to the material without any treatment. However, depending on the proportions between non-toxic salt and oxide-reducing salt, there is a better surface finishing, which contributes to the environment, as it avoids the generation of cyanide and cyanate-based residues.